We next consider the complete solution (composed of both homogeneous
and particular solutions) of the 2nd order DE
![$\displaystyle y''(t)+2\zeta\omega_n y'(t)+\omega_n^2 y(t)=x(t)$](img659.svg) |
(232) |
with a unit step
input and zero initial conditions
. As the input is a constant for
, we can
assume the particular solution to be a constant
with zero
derivatives
. Substituting these into the DE above,
we get
, i.e., the steady state solution is:
![$\displaystyle y_{ss}(t)=y_p(t)=y(\infty)=\frac{1}{\omega_n^2}$](img665.svg) |
(233) |
The complete response can be obtained as the sum of the homogeneous
solution (same as that obtained previously) and particular solution,
corresponding to the transient and steady state response, respectively:
![$\displaystyle y(t)=y_h(t)+y_p(t)=C_1 e^{s_1t}+C_2 e^{s_2t}+\frac{1}{\omega_n^2}$](img666.svg) |
(234) |
The two coefficients
and
can be obtained based on the two
zero initial conditions:
Solving these equations we get:
![$\displaystyle C_1=\frac{s_2}{\omega_n^2(s_1-s_2)}=\frac{-s_2}{\omega_n^2(s_2-s_1)},
\;\;\;\;\;\;C_2=\frac{s_1}{\omega_n^2(s_2-s_1)}$](img669.svg) |
(236) |
Now the complete solution becomes:
![$\displaystyle y(t)=\frac{1}{\omega_n^2}\left[1-\left(\frac{s_2e^{s_1t}}{s_2-s_1...
...ht]
=\frac{1}{\omega_n^2}\left(1-\frac{s_2e^{s_1t}-s_1e^{s_2t}}{s_2-s_1}\right)$](img670.svg) |
(237) |
Alternatively, the nonhomogeneous 2nd-order LCCODE given above can
be converted into a 1st-order ODE system and solving which we obtain
the same results, as shown
here.
The two roots
and
take different forms depending on
whether the discriminant
is greater
or smaller than 0, i.e., whether
is greater or smaller then 1.
Here we only consider the case when
, i.e.,
,
for an under-damped second order system. The two roots are
and![$\displaystyle \;\;\;\;s_2-s_1=-2j\omega_d$](img675.svg) |
(238) |
where
is the damped natural frequency:
![$\displaystyle \omega_d=\omega_n\sqrt{1-\zeta^2}$](img651.svg) |
(239) |
Finally the complete solution of the non-homogeneous DE is:
where
and![$\displaystyle \;\;\;\;
\sin \phi=\sqrt{1-\zeta^2},\;\;\;\;\cos \phi=\zeta$](img683.svg) |
(241) |
The step response
can be characterized by two parameters:
- Rise time:
The rise time
is the time at which
reaches
of the
steady state value
(assumed to be 1 for simplicity):
or![$\displaystyle \;\;\;\;\;
\frac{e^{-\zeta\omega_nt_r}}{\sqrt{1-\zeta^2}} \sin(\omega_dt_r+\phi)=0$](img688.svg) |
(242) |
i.e.,
or![$\displaystyle \;\;\;\;\;
\omega_dt_r+\phi=\pi$](img690.svg) |
(243) |
Solving for
we get
![$\displaystyle t_r=\frac{\pi-\phi}{\omega_d}=\frac{\pi-\phi}{\omega_n\sqrt{1-\zeta^2}}$](img691.svg) |
(244) |
But as
, taking arctangent
on both sides we get
i.e.![$\displaystyle \;\;\;\;\;
t_r=\frac{\pi-\phi}{\omega_d}
=\frac{1}{\omega_n\sqrt{1-\zeta^2}} \tan^{-1}\left(-\frac{\sqrt{1-\zeta^2}}{\zeta}\right)$](img694.svg) |
(245) |
- Peak time:
The peak time
is the time at which
reaches the first peak, which can be
found by setting the time derivative of
to zero, yielding
![$\displaystyle \zeta\omega_ne^{-\zeta\omega_nt} \sin(\omega_dt+\phi)
=e^{-\zeta\omega_nt} \omega_d\cos(\omega_dt+\phi)$](img696.svg) |
(246) |
i.e.,
![$\displaystyle \zeta\omega_n \sin(\omega_dt+\phi)=\omega_n\sqrt{1-\zeta^2}\cos(\omega_dt+\phi)$](img697.svg) |
(247) |
or
![$\displaystyle \tan(\omega_dt+\phi)=\frac{\sqrt{1-\zeta^2}}{\zeta}=\tan\phi$](img698.svg) |
(248) |
We get
for the first peak, i.e.,
![$\displaystyle t_p=\frac{\pi}{\omega_d}=\frac{\pi}{\omega_n\sqrt{1-\zeta^2}}$](img700.svg) |
(249) |
Substituting
inito
we get the peak value:
The overshoot is
.
In particular, if
and therefore
, we have
![$\displaystyle y(t)=\frac{1}{\omega_n^2}\left[1-\sin(\omega_n t+\pi/2)\right]
=\frac{1}{\omega_n^2}\left[1-\cos(\omega_n t)\right]$](img705.svg) |
(251) |
The plots below shows an example with
. Note the critical
damped case when
. An overshoot will occur for any
.
The step response is plotted below. Note that
and
.
Example
Consider the response
of an undamped 2nd order RCL system.
- Find the response
of the RLC circuit to a step input
.
The general solution is the sum of the homogeneous solution
and the particular solution
:
![$\displaystyle y(t)=V+A\sin(\omega_nt)+B\cos(\omega_nt),\;\;\;\;\;\;\;t>0$](img713.svg) |
(252) |
Consider two different sets of initial conditions:
- Find the system's response to a square impulse
![$\displaystyle x(t)=\left\{ \begin{array}{ll}1 & 0\le t< t_0 \\ 0 & \mbox{else}
\end{array} \right.$](img722.svg) |
(255) |
As
, the response is
![$\displaystyle y(t)=[1-\cos(\omega_nt)]u(t)-[1-\cos(\omega_n(t-t_0))]u(t-t_0)$](img724.svg) |
(256) |
When
, we have
![$\displaystyle y(t)=\cos(\omega_n(t-t_0))-\cos(\omega_nt)$](img726.svg) |
(257) |
We further consider two special cases.
- When
, we have
This is a one period of a sinusoid.
- When
, we have
This is a pure sinusoid after
.
- Find the impulse response
. The input
is an impulse which
can be written as
![$\displaystyle x(t)=\delta(t)=\lim_{t_0\rightarrow 0}\left\{ \begin{array}{cl}
1/t_0 & 0\le t< t_0 \\ 0 & \mbox{else} \end{array}\right.$](img736.svg) |
(260) |
When
, we have first order approximations
and
,
and we get
![$\displaystyle \cos(\omega_n(t-t_0))=\cos(\omega_nt)\;\cos(\omega_nt_0)+\sin(\omega_nt)\;
\sin(\omega_nt_0) \approx\cos(\omega_nt)+\sin(\omega_nt)\,\omega_nt_0$](img740.svg) |
(261) |
Substituting this into
we get the impulse response
![$\displaystyle y(t)=\omega_n\sin(\omega_nt)$](img742.svg) |
(262) |
- It is often desirable for a second order system to reach a set steady
state value without overshoot. This can be achieved by driving the system
by an impulse
with response
, followed
by a step
with response
![$\displaystyle [1-\cos(\omega_n(t-T/4))]u(t-T/4)=[1-\cos(\omega_nt-\pi/2)]u(t-T/4)
=[1-\sin(\omega_nt)]u(t-T/4)$](img746.svg) |
(263) |
The total response is
![$\displaystyle y(t)=\sin(\omega_nt)u(t)+[1-\sin(\omega_nt)]u(t-T/4)
=\left\{\begin{array}{cl} \sin(\omega_nt) & 0<t<T/4 \\
1 & t>T/4\end{array} \right.$](img747.svg) |
(264) |
We see that after
reaches the first peak of
at
, it will
stay at the constant value
as the two responses cancel each other for
.
- Alternatively, the steady state value
can be achieved without
overshoot by applying an input
. The response to
is
![$\displaystyle \frac{1}{2}[1-\cos(\omega_nt)]u(t)$](img754.svg) |
(265) |
while the response to
is
![$\displaystyle \frac{1}{2}[1-\cos(\omega_n(t-T/2))]u(t-T/2)
=\frac{1}{2}[1-\cos(\omega_nt-\pi)]u(t-T/2)
=\frac{1}{2}[1+\cos(\omega_nt)]u(t-T/2)$](img756.svg) |
(266) |
The overall response is the difference between the two individual responses:
![$\displaystyle y(t)=\left\{\begin{array}{cl}
[1-\cos\omega_nt]/2 & 0<t<T/2 \\ 1 & t>T/2 \end{array} \right.$](img757.svg) |
(267) |
i.e., the response is
for all
.
- It is desirable for a second order system to reach a steady state value
within a time delay
without overshoot. We first consider
driving the system with a positive square pulse of value
followed
by a negative one of
:
![$\displaystyle x(t)=\left\{\begin{array}{cl}
V & (0<t<t_0/2) \\ (1-a)V & (t_0/2<t<t_0)
\end{array}\right. =V \left[u(t)-a u(t-t_0/2)\right]$](img762.svg) |
(268) |
The response for
is:
![$\displaystyle y(t)=V\left[ 1-\cos(\omega_nt)-a[1-\cos(\omega_n(t-t_0/2))]\right]$](img764.svg) |
(269) |
In order for the output to be a constant
for
, we need to
have the input
for
, and set the initial conditions at
to be
and
. To do so, we let
![$\displaystyle \frac{dy(t)}{dt}\bigg\vert _{t=t_0}=V\omega_n\left[ \sin(\omega_n...
...right]_{t=t_0}
=V\omega_n\left[ \sin(\omega_nt_0)-a\sin(\omega_nt_0/2)\right]=0$](img769.svg) |
(270) |
Based on the trigonometric identity
, the equation above
can be written as
![$\displaystyle 2\cos(\omega_nt_0/2) =a$](img771.svg) |
(271) |
Substituting this into the desired initial condition
, we get
![$\displaystyle y(t_0)=V\left[ 1-\cos(\omega_nt_0)-2\cos(\omega_nt_0/2)
[1-\cos(\omega_n(t_0/2))]\right]
=2V(1-\cos(\omega_nt_0/2) =4V\sin^2(\omega_nt_0/4)=1$](img772.svg) |
(272) |
where we have used the trigonometric identities
and
. Solving this for
we get
![$\displaystyle V=\frac{1}{4\sin^2(\omega_nt_0/4)}$](img775.svg) |
(273) |
As now we have the initial conditions
and
as
needed. If we set
for
, so that the output will be at
constant
when
.